2008
DOI: 10.1002/dvdy.21719
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial expression of collagens during murine atrioventricular heart valve development and maintenance

Abstract: Heart valve function is achieved by organization of matrix components including collagens, yet the distribution of collagens in valvular structures is not well defined. Therefore, we examined the temporal and spatial expression of select fibril-, network-, beaded filament-forming, and FACIT collagens in endocardial cushions, remodeling, maturing, and adult murine atrioventricular heart valves. Of the genes examined, col1a1, col2a1, and col3a1 transcripts are most highly expressed in endocardial cushions. Expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 36 publications
0
58
0
Order By: Relevance
“…The increased collagen amounts and concentric remodeling seen in the wild type mice during early response to aortic banding may lead to increased cardiac stiffness and counteract development of left ventricular dilatation in the acute phase. We and others have previously reported that collagen isoforms are differently expressed during myocardial remodeling irrespective of heart failure (51,52). Interestingly, we found in paper II that although total collagen content in the left ventricle was increased in animals with heart failure compared to those without, there was no difference in collagen I or III protein levels between the two groups.…”
Section: Fibrillar Collagens In Pressure Overloadmentioning
confidence: 44%
“…The increased collagen amounts and concentric remodeling seen in the wild type mice during early response to aortic banding may lead to increased cardiac stiffness and counteract development of left ventricular dilatation in the acute phase. We and others have previously reported that collagen isoforms are differently expressed during myocardial remodeling irrespective of heart failure (51,52). Interestingly, we found in paper II that although total collagen content in the left ventricle was increased in animals with heart failure compared to those without, there was no difference in collagen I or III protein levels between the two groups.…”
Section: Fibrillar Collagens In Pressure Overloadmentioning
confidence: 44%
“…Fibrillogenesis in skin is also fine-tuned by the SLRPs decorin and lumican, which limit lateral growth of the fibril; mice lacking either of these SLRPs have increased fibril diameter in the dermis and fragile skin (Chakravarti et al 1998;Danielson et al 1997; Table 1). In the heart, fibrillar collagens have been implicated in ventricular myocardial morphogenesis and heart valve development (Peacock et al 2008), as shown in fetal mice deficient in collagens V and XI (Lincoln et al 2006). Therefore, tissue development and function relies on a structurally integral ECM formed by the proper assembly of its components.…”
Section: Early Embryonic Development Requires a Proper Basement Membranementioning
confidence: 98%
“…As remodeling procedes, collagen fibrils become densely packed locally at the outflow side of the leaflet and loosely arranged and interweaving elsewhere (Aikawa et al 2006;Hinton et al 2006;Peacock et al 2008;Tan et al 2011). Fibrillogenesis is promoted by periostin, a multifunctional fascilin-domain-containing protein (Norris et al 2009).…”
Section: Remodeling Of the Ecmmentioning
confidence: 99%
“…The elongation of the valve leaflets and stratification of the ECM begins late in gestation and continues postnatally (Aikawa et al 2006;Hinton et al 2006;Kruithof et al 2007;Peacock et al 2008;Stephens et al 2010). Initial ECM patterning along the AV leaflet axis occurs between E15.5 and E18.5 through a transient increase in cell density called condensation (Kruithof et al 2007).…”
Section: Remodeling Of the Ecmmentioning
confidence: 99%